Seasonal variations in chemical composition and stable isotopes of farmed and wild Brazilian freshwater fish - Sant'Ana, Lea Silvia [UNESP]; Ducatti, Carlos; Ramires, Djalma Goncalves [UNESP] (Elsevier B.V., 2010)
This study examined variations in the Fulton condition factor, chemical composition, and stable isotopes of carbon and nitrogen in the Brazilian freshwater fish cachara (Pseudoplatystoma fasciatum), comparing farmed and wild fish in different seasons. Values for energy, protein, moisture, and Fulton's condition factor were higher for farmed than for wild fish in the rainy season, indicating better nutritional quality; however, these differences were not observed in the dry season. Likewise, we found significant enhancement of delta(15)N in farmed fish in the rainy season but not in the dry season, whereas enhancement of delta(13)C was observed in both seasons. The combined measurement of delta(13)C and delta(15)N provided traceability under all conditions. Our findings show that stable isotope analysis of C and N can be used to trace cachara origin, and that seasonal variations need to be considered when applying chemical and isotopic authentication of fish and fish products. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Traceability; Cachara; Pseudoplatystoma fasciatum; (13)C; (15)N; Seasonality